Poster presentation Assessing the cytotoxic, estrogenic and mutagenic effects of pharmaceutical residues and their photo-transformation products in water - Vasquez Christodoulou, Marlen (My University, 2026)
Tarapoulouzi M, Vasquez MI, Lambrianides N, Felekkis K, Sticht C, Saile M, Gretz N, Fatta-Kassinos D, Assessing the cytotoxic, estrogenic and mutagenic effects of pharmaceutical residues and their photo-transformation products in water, Poster presentation, Workshop Novel tools and methods for the screening of chemicals for developmental neurotoxicity, DENAMIC, Amsterdam, The Netherlands, 10-11 March 2014.